40th AIAA Aerospace Sciences Meeting &Amp; Exhibit 2002
DOI: 10.2514/6.2002-299
|View full text |Cite
|
Sign up to set email alerts
|

Study of the separated high enthalpy flow around a double cone

Abstract: High enthalpy flow separation over bodies at hypersonic speeds continues to intrigue researchers, since considerable differences are observed between experiments and CFD. In the present study the separated flow field around a double cone has been investigated at nominal stagnation enthalpies of 4.2 MJ/kg and 1.6 MJ/kg. The flow around a double cone (first cone semi-apex angle = 25°; second cone semiapex angle=68°) has been visualized using highspeed image converter camera (IMACON) and double exposure holograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Thus, the relationship between the luminescence of TSP and the temperature is expressed by transforming Eqs. (1)(2)(3):…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the relationship between the luminescence of TSP and the temperature is expressed by transforming Eqs. (1)(2)(3):…”
Section: Theorymentioning
confidence: 99%
“…Both the type of thermal protection system and its weight are determined by the heat flux data provided from wind-tunnel tests and/or computational fluid dynamics (CFD) results. In wind-tunnel tests, various types of conventional thermal sensors are used to measure the quantitative heat flux [1][2][3]. They are all point sensors capable of measuring the heat flux only at spatially discrete points.…”
Section: Introductionmentioning
confidence: 99%
“…From both infinite fringe interferometry and shadowgraphy, the ratio of separation point from the leading edge to the face length of the first cone is found to be 0.3. For details on the location of the separation point and the measured separation length, see Jagadeesh et al (2002). However, these interferometric studies revealed the shock structure recorded at various times during the steady flow test window to be different.…”
Section: Methodsmentioning
confidence: 99%